Bioaccumulation and Toxicity of Copper and Lead in Chlorella vulgaris - Regaldo, Luciana María (2013)
This article presents an advance to the knowledge in the solution of heavy metal environmental pollution using living microalgae cells. The study aims to evaluate the toxic effects of copper and lead on the growth of Chlorella vulgaris (Beijerinck Novakova, 1890) and to assess its bioaccumulation capacity as a function of the metals concentration and the time of contact with the metals. Growth inhibition was greater with Cu than Pb. For both metals, the removal efficiency was very fast and decreased with the increase in metal concentration, and the removal efficiency increased with the exposure time. Living algae removed up to 98.7 % of Pb when exposed to low concentrations after 1 hour and exposure and up to 81.97% and 92.53% of Cu after 10 min and 12 h of exposure, respectively. The final metal concentrations in the supernatant and in the microalgae were significant and negatively correlated, which demonstrated the efficiency of C. vulgaris in removing metals from wastewaters. Microalgae reduced Cu and Pb from ppm to ppb concentrations in a very short time, so it is recommended for larger scale treatments. Keywords: Bioremediation; bioaccumulation; Chlorella vulgaris; heavy metal removal; water pollution control.